Os jogos eletrônicos em aulas de educação física no ensino fundamental: um olhar geral - Silva, Yan Periotto Gonçalves da (Universidade Federal de São Carlos, 2024)
Since 2017, electronic games have been included in the school Physical Education curriculum through the National Common Curricular Base (BNCC). This addition seems appropriate since we, as future teachers, are always in contact with students who have different interests and potentialities that can be approached in class in the most diverse ways, including the use of available technological means or, from these means, convert them into an educational setting. Furthermore, electronic games are part of the vast majority of the population of children and adolescents, whether on cell phones or desktop computers (notebooks, desktops) and many use them as entertainment. Due to the recent Covid-19 pandemic and the necessary social isolation, this interaction seems to have become more present and users share their interests and achievements in games with their colleagues/friends even from a distance. Based on these considerations, the objective of this research was to analyze the teaching and learning process of the thematic unit of electronic games in Physical Education classes. For this, we used qualitative research, in which a 7th year class of elementary school, final years, belonging to a state public school in the city of São Carlos/SP was monitored. The data collection instruments were field diaries, prepared by the researcher after each class taught by the Physical Education teacher, as well as a semi-structured interview with the teacher in question and a questionnaire for the students. After collecting and qualitatively analyzing the data, we arrived at the following categories: a) Learning potentials, which dealt with how electronic games contribute through different relationships between generations, how cell phone or computer applications contribute to access health, as well as the approximation of the thematic unit of games and games and the approximation of the virtual to the real; b) Pedagogical practice, where the teacher's strategies, the coexistence between students and teacher were observed, in addition to class time and the exchange of knowledge; c) Availability of access (content, courses, alternative proposals), the latter dealt with the lack of specific training in the area and the importance of the continuous relationship between university and school. In this way, the records sought to create possibilities for future interventions in gamification processes, with electronic games as a background as a learning tool in Physical Education classes through playful activities with adapted contextualized games.
Electronic games in physical education classes in elementary education: a general overview
Keywords: Educação física escolar; Jogos eletrônicos; Gamificação; School physical education; Electronic games; Gamification; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM